PENGEMBANGAN E-LKPD BERBASIS GUIDED INQUIRY TERINTEGRASI STEM PADA MATERI ASAM BASA - Molani Paulina Hasibuan; Ratih Permana Sari; Hamidah Nasution (Jurnal Penelitian Pendidikan IPA, 2023)
The development of technology and science in the 21st century has been running very rapidly, with these developments students need to be equipped with 21st century skills to be able to compete in the era of globalization, especially in the field of education. The lack of use of learning media causes low motivation and interest in learning for students in understanding acid-base material. This can be proven based on a needs analysis of five chemistry teachers at public high schools in Langsa City. This study aims to determine the feasibility and attractiveness and responses of students about the Student Worksheet Based Guided Inquiry Integrated STEM on acid-base materials. This study uses the R&D model ADDIE. The instruments used in this study were a material and media expert validation questionnaire, a teacher response questionnaire and a student response questionnaire. The results of the student worksheet analysis showed that the validation assessments of material experts, media experts, teacher responses and student responses each reached a percentage of 84.8%, 89.34%, 89.82% and 95.56%, which means that student worksheet Based Guided Inquiry Integrated STEM on acid-base material is very suitable to be used as teaching material and the attractiveness criteria of student worksheet is very interesting